2021
DOI: 10.1186/s13287-021-02330-9
|View full text |Cite
|
Sign up to set email alerts
|

Human bone marrow-derived, pooled, allogeneic mesenchymal stromal cells manufactured from multiple donors at different times show comparable biological functions in vitro, and in vivo to repair limb ischemia

Abstract: Background We have previously demonstrated that a pooled population of bone marrow-derived, allogeneic mesenchymal stromal cells (BMMSC), Stempeucel®-1, produced under good manufacturing practices (GMP) conditions, showed clinical efficacy and safety in patients suffering from critical limb ischemia (CLI) due to Buerger’s disease. While Stempeucel®-1 is currently used for CLI and other clinical indications, we wanted to ensure that the product’s continuity is addressed by developing and charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Donor-to-donor variability and extensive in vitro expansion are major drivers of inconsistent results from clinical trials, particularly when hMSCs batches are manufactured from single donors (3,56). Pooling single donations, a concept implemented for platelet concentrates for many years (57), has been introduced recently for both hMSC and hPL products (13,16,19,20,25,58). To balance the needs for scale-up and low-level expansion of a pooled hMSC product, our concept starts with MCBs from single donor hMSCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Donor-to-donor variability and extensive in vitro expansion are major drivers of inconsistent results from clinical trials, particularly when hMSCs batches are manufactured from single donors (3,56). Pooling single donations, a concept implemented for platelet concentrates for many years (57), has been introduced recently for both hMSC and hPL products (13,16,19,20,25,58). To balance the needs for scale-up and low-level expansion of a pooled hMSC product, our concept starts with MCBs from single donor hMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…We argued about the best pooling time point. C o n t r a r y t o " M S C -F F M " , p o o l e d a s M N C s , a n d "Stempeucel ® ", pooled at passage 1 followed by five to six expansion passages (17,20), we compared pooling at passage 1, 2 and 3. As expected, the in vitro tests showed that quality did not differ significantly between the different hMSC pools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for continued efficacy of Stempeucel after a single administration was the localized injection of cells at the site of ischemia (infrapopliteal region); these cells predominantly stay localized at the injection site for a minimum duration of 28 days, as shown in our biodistribution studies conducted in a limb ischemia murine model using labeled cells. 30 Stempeucel is capable of secreting a variety of bioactive factors with diverse functional activity, especially those that have been implicated in angiogenesis and anti‐inflammatory properties, such as VEGF, TGF‐β, HGF, angiopoietin 1 and 2, IL‐8, Indoleamine 2,3‐DiOxygenase (IDO), and Prostaglandin E2 (PGE2), among others. This may result in continued improvement as seen in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The source of stem cells or EVs is regarded as another problem, since the isolation and expansion of autologous stem cells commonly used in clinical trials are inconvenient and time-consuming. However, commercial allogeneic stem cells like Stempeucel® began available and used in clinical recently 66 , 67 . These commercial cells could be a source in the future.…”
Section: Challenges For Stem Cells or Evs-based Therapy In Cns Disord...mentioning
confidence: 99%